1978
DOI: 10.2136/sssaj1978.03615995004200020010x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Micronutrient Cations in Soil Under Conditions of Varying Redox Potential and pH

Abstract: A laboratory study was conducted to determine the influence of redox potential and soil pH on the distribution of Fe, Mn, Zn, and Cu in Mhoon silty clay loam soil (Typic Fluvaquents) and to provide insight into factors affecting micronutrient dissolution and mobility in soil. Generally, greater amounts of Fe, Mn, Zn, and Cu were found in the Na acetate (exchangeable) and pyrophosphate (organic) extractions at low pH and Eh than at high pH or Eh. In contrast, the amounts (except Mn) in the water‐soluble, NH2OH·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1
18

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 0 publications
8
61
1
18
Order By: Relevance
“…In long term studies, however, much lower concentrations of iron chelates (<10 LM) are sufficient to cover the iron demand for optimal growth (8, and unpublished data). In soil solutions, depending upon the pH and the redox potential of the soils, a high proportion of iron can be observed as complexed iron (17). Concentrations of complexed iron in soil solutions as hydroxamate siderophores between 10-8 and 10-7 M were found by Powell et at (13).…”
Section: Romheld and Marschnermentioning
confidence: 86%
“…In long term studies, however, much lower concentrations of iron chelates (<10 LM) are sufficient to cover the iron demand for optimal growth (8, and unpublished data). In soil solutions, depending upon the pH and the redox potential of the soils, a high proportion of iron can be observed as complexed iron (17). Concentrations of complexed iron in soil solutions as hydroxamate siderophores between 10-8 and 10-7 M were found by Powell et at (13).…”
Section: Romheld and Marschnermentioning
confidence: 86%
“…Sulphide minerals are normally oxidised to sulphates at higher Eh levels (Evans, 1989). Sims and Patrick (1978) observed that water soluble Zn decreased at low Eh. However, the opposite was recorded by these authors for Cu and exchangeable (sodium acetate-extractable) concentrations of both Zn and Cu increased at low Eh.…”
Section: Redox Potentialmentioning
confidence: 99%
“…Em solos ácidos, como também observado por Xiang et al (1995) (Sims & Patrick, 1978;Iyengar et al, 1981).…”
Section: Resultsunclassified